Endoscopic closure of an anastomo-cutaneous fistula: Filling and shielding using polyglycolic acid sheets and fibrin glue with easily deliverable technique - Kawabata, Hideaki (Endosc Int Open, 2018)
Background and study aims  Recently, endoscopic closure of gastrointestinal fistulas using polyglycolic acid (PGA) sheets with fibrin glue (FG) has been attempted. A 70-year-old woman who had undergone pancreaticoduodenectomy for pancreatic cancer suffered from a refractory anastomo-cutaneous fistula at the site of gastro-jejunostomy. We attempted endoscopic closure with filling and shielding using PGA sheets and FG. After introducing a guidewire into the fistula, a small piece of PGA sheet was skewered onto the guidewire and then pushed using a tapered catheter over the guidewire and delivered into the fistula. A total of 10 sheets were delivered via the same procedure. Next, the mucosa around the fistula was ablated, and the orifice of the fistula along with the surrounding mucosa was shielded with a piece of PGA sheet fixed with hemoclips and FG. After this procedure, the leakage disappeared and the fistula was undetectable on contrast radiograms. Endoscopic closure of anastomo-cutaneous fistula with filling and shielding using PGA sheets and FG is an effective, safe, low-invasive treatment, and the filling technique using a guidewire ensures a safe, smooth procedure.